How useful is core inflation for forecasting headline inflation? - Bermingham, Colin (Economic & Social Studies, 2007)
The paper constructs various core inflation measures. These include various trimmed means using disaggregated data and a structural VAR estimate of core inflation for Ireland. The ability of these core inflation measures to forecast future headline inflation is compared using a regression model. An ARIMA model fitted to the headline inflation rate is used as the benchmark forecast. The forecasts from the ARIMA model are most accurate over short time horizons for monthly data. The structural VAR based estimate is most accurate over longer time horizons. For quarterly data, the structural VAR provides the optimal forecast over all time horizons.
Keywords: Inflation; Forecasting; Quantitative economics